2012 13th International Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems 2012
DOI: 10.1109/esime.2012.6191713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isothermal aging and salt spray tests on reliability and mechanical strength of eutectic Sn-Bi lead-free solder joints

Abstract: Eutectic Sn-Bi solder has attracted a great deal of interest since it offers good reliability comparable to that of Sn-Pb solders. Additionally, the increasing need for low cost manufacturing processes, particularly in consumer electronics, has made it an interesting alternative. This paper presents reliability and microstructural studies of eutectic 42%Sn-58%Bi (wt.%) lead-free solder alloy. The reliability was investigated using two different accelerated environmental tests. The first test series was subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In recent twenty years, lead-free solders have made great development and several main kinds of Sn-based lead-free solders such as Sn-Ag [6,7], Sn-Zn [8,9], Sn-Bi [10,11], Sn-Cu [12,13], and Sn-Ag-Cu [14,15] have been fiercely studied by researchers. Among these most promising lead-free solder alloys, however, the Sn-Bi solder alloys have better properties such as lower melting temperature, good tensile strength, good reliability, and well creep resistance [16][17][18]. The eutectic Sn-58Bi solder has a low melting point of 139 ∘ C [19,20] and it is lower than 183 ∘ C of the eutectic Sn-Pb solder which consists of 63 wt.% Sn and 37 wt.% Pb [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent twenty years, lead-free solders have made great development and several main kinds of Sn-based lead-free solders such as Sn-Ag [6,7], Sn-Zn [8,9], Sn-Bi [10,11], Sn-Cu [12,13], and Sn-Ag-Cu [14,15] have been fiercely studied by researchers. Among these most promising lead-free solder alloys, however, the Sn-Bi solder alloys have better properties such as lower melting temperature, good tensile strength, good reliability, and well creep resistance [16][17][18]. The eutectic Sn-58Bi solder has a low melting point of 139 ∘ C [19,20] and it is lower than 183 ∘ C of the eutectic Sn-Pb solder which consists of 63 wt.% Sn and 37 wt.% Pb [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the great finding from the lead-free solder related research, it was found that the main disadvantages of the lead-free solder is high melting temperature [3], [4], [5], insufficient fatigue resistance and low reliability characteristic inhibit wide practical application in industry [6]. The increase of melting temperature in lead-free solder has already been a disadvantages to the manufactures since it leading to significant capital expenditure and resulting in the increase of product cost [7].…”
Section: Introductionmentioning
confidence: 99%